The Internet - a risk-taking space for university students - Wylęgły, Kamila (Journal of Education Culture and Society, 2021)
Aim. The purpose of this article is to analyse risky behaviours undertaken by university students on the Internet.Theory. The concepts of “risk” and “risky behaviour” are known and often discussed in science. Krzysztof Ostaszewski (2005) defines risky behaviours as actions that contradict social norms and legal order, which at the same time pose a threat to a person's health and development. The catalogue of risky behaviours is very diverse and—more importantly—open. With the development of civilisation, new forms appear. Examples include risky behaviours on the Internet.Methodology and research results. The study population sample consisted of 241 university students. The research was conducted using an online survey questionnaire. The respondents admitted to taking risks in the virtual world. A large percentage of respondents admit to sharing private information on social networks (almost 70%). Nearly 75% of respondents ignore communications about potential threats to websites, putting themselves at risk of losing sensitive data. Moreover, 65.1% of students admit to downloading content from illegal sources. Other risky behaviours undertaken by students on the Internet include Internet addiction and online activities, aggression on the Internet, sexual and/or erotic behaviour in cyberspace. The paper also presents the answers to open-ended questions, which refer to threats on the Internet as perceived by the students. The answers given most often referred to: addiction to new technologies, loss/theft of private data, vulnerability to false/unverified information available on the Internet.Cognitive value. Online risk-taking is a global problem. The phenomenon should be further theoretically considered and analysed in a pedagogical practice.